The crimson skew - Grove, S. E. (Grove, S. E. Mapmakers, 2016)
In a world transformed by 1799's Great Disruption--when all of the continents were flung into different time periods, Sophia Tims journeys home to Boston, anticipating her reunion with Theo, but he has been conscripted to fight in the Western War, Prime Minister Broadgirldle's twisted vision of Manifest Destiny.